Predictors of outcomes of total knee replacement surgery. - Judge, A; Arden, N; Cooper, C; Kassim Javaid, M; Carr, A; Field, R; Dieppe, P (2012)
OBJECTIVE: To identify pre-operative predictors of patient-reported outcomes of primary total knee replacement (TKR) surgery. METHODS: The Elective Orthopaedic Centre database is a large prospective cohort of 1991 patients receiving primary TKR in south-west London from 2005 to 2008. The primary outcome is the 6-month post-operative Oxford Knee Score (OKS). To classify whether patients had a clinically important outcome, we calculated a patient acceptable symptom state (PASS) for the 6-month OKS related to satisfaction with surgery. Potential predictor variables were pre-operative OKS, age, sex, BMI, deprivation, surgical side, diagnosis, operation type, American Society of Anesthesiologists grade and EQ5D anxiety/depression. Regression modelling was used to identify predictors of outcome. RESULTS: The strongest determinants of outcome include pre-operative pain/function-those with less severe pre-operative disease obtain the best outcomes; diagnosis in relation to pain outcome-patients with RA did better than those with OA; deprivation-those living in poorer areas had worse outcomes; and anxiety/depression-worse pre-operative anxiety/depression led to worse pain. Differences were observed between predictors of pain and functional outcomes. Diagnosis of RA and anxiety/depression were associated with pain, whereas age and gender were specifically associated with function. BMI was not a clinically important predictor of outcome. CONCLUSION: This study identified clinically important predictors of attained pain/function post-TKR. Predictors of pain were not necessarily the same as functional outcomes, which may be important in the context of a patient's expectations of surgery. Other predictive factors need to be identified to improve our ability to recognize patients at risk of poor TKR outcomes.